Polyamines in Halophytes - Bueno, Milagros; Cordovilla, María-Pilar (Frontiers in Plant Science, 2019)
Polyamines are related to many aspects of the plant’s life cycle, including responses to biotic and abiotic stress. On the other hand, halophytic plants are useful models for studying salt tolerance mechanisms related to the adaptive strategies that these plants present in adverse environments. Furthermore, some halophytes have high economic value, being recommended instead of glycophytes as alternative agricultural crops in salt-affected coastal zones or saline farmlands. In recent years, the understanding of the role of polyamines in salt-tolerant plants has greatly advanced. This mini-review reports on the advances in the knowledge of polyamines and their participation in achieving better salt tolerance in 10 halophytes. Polyamines are associated with responses to heavy metals in phytoremediation processes using certain salt-tolerant species (Atriplex atacamensis, Atriplex halimus, Inula chrithmoides, and Kosteletzkya pentacarpos). In crops with exceptional nutritional properties such as Chenopodium quinoa, polyamines may be useful markers of salt-tolerant genotypes. The signaling and protection mechanisms of polyamines have been investigated in depth in the extreme halophyte Mesembryanthemum crystallinum and Thellungiella spp., enabling genetic manipulation of polyamine biosynthesis. In Prosopis strombulifera, different biochemical and physiological responses have been reported, depending on the type of salt (NaCl, Na2SO4). Increases in spermidine and spermine have been positively associated with stress tolerance as these compounds provide protection in Cymodocea nodosa, and Solanum chilense, respectively. In addition, abscisic acid and salicylic acid can improve the beneficial effect of polyamines in these plants. Therefore, these results indicate the great potential of polyamines and their contribution to stress tolerance.